HUBUNGAN PERAWATAN PAYUDARA DENGAN PRODUKSI ASI IBU NIFAS DI RUANG EDELWEYS BAWAH RUMAH SAKIT BHAYANGKARA TKT III MANADO - Soputan, Monica; Kairupan, Michelle (Journal Of Community & Emergency, 2024)
Breast milk is the most important baby food, especially in the first months of life. Breast milk as a single food will be sufficient to meet the needs of normal baby growth and development until the age of 4-6 months. Based on data from the World Health Organization (WHO) in 2015, it is estimated that 130 million babies are born in the world every year and 4 million babies die in the first 28 days of life. To reduce morbidity, WHO recommends that newborns receive exclusive breastfeeding (without additional food) for at least six months. The purpose of this study was to determine the relationship between breast care and breast milk production for postpartum mothers in the Edelweys room at the Bhayangkara Hospital Manado. The type of research used in this research is descriptive analytic with a cross sectional study approach. The population in this study were all postpartum mothers in the Edelweys room with a total of 31 samples. The data were analyzed using the chi-square test with a significance value of = 0.005. Based on the results of statistical tests using the chi square test, the fisher's exact test value was obtained with a value of -value = 0.002 which is smaller than the value of = 0.05. It means that H0 is rejected, then there is a relationship between breast care and postpartum mother's milk production in the Edelweys Room at the Bhayangkara Hospital Manado. The conclusion in this study is that breast care for postpartum mothers in the Edelweys room at Bhayangkara Hospital is mostly not carried out. The production of breast milk in postpartum mothers in the Edelweys room at Bhayangkara Hospital Manado is mostly with non-smooth production. There is a Relationship between Breast Care and Breast Milk Production in Postpartum Mothers in the Edelweys Room at the Bhayangkara Hospital Manado.